Slavery and Industrialization: Williams Redux - Burnard , Trevor (Comparativ, 2021)
This paper evaluates the standing of Eric Williams, author of the classic work on capitalism and slavery 75 years ago, in the light of new scholarship, notably by historians writing as part of the New History of Capitalism movement. It emphasises how one part of Williams’ argument is especially persuasive, that in the period between 1688 and 1763 all sections of British society supported the planter interest in the Americas and thus slavery without reservation. The Seven Years’ War marked, in retrospect, the peak of planter power within the British Empire. The American Revolution, by contrast, formed, as Williams suggested, a crisis in plantation societies but more so, at least economically, for the American South than for the British Caribbean.